Development of Laboratory-scale Lamb Wave-based Health Monitoring System for Laminated Composites - Leonardo Gunawan; Muhammad Hamzah Farrasamulya; Andi Kuswoyo; Tatacipta Dirgantara (Journal of Engineering and Technological Sciences, 2021)
This paper presents the development process of a laboratory-scale Lamb wave-based structural health monitoring (SHM) system for laminated composite plates. Piezoelectric patches are used in pairs as actuator/sensor to evaluate the time of flight (TOF), i.e. the time difference between the transmitted/received signals of a damaged plate and those of a healthy plate. The damage detection scheme is enabled by means of evaluating the TOF from at least three actuator/receiver pairs. In this work, experiments were performed on two GFRP plates, one healthy and the other one with artificial delamination. Nine piezoelectric transducers were mounted on each plate and the detection of the delamination location was demonstrated, using 4 pairs and 20 pairs of actuators/sensors. The combinations of fewer and more actuators/sensor pairs both provided a damage location that was in good agreement with the artificial damage location. The developed SHM system using simple and affordable equipment is suitable for supporting fundamental studies on damage detection, such as the development of an algorithm for location detection using the optimum number of actuator/sensor pairs.